محدودية الخطاب المسجدي بوادي سوف وآفاق تطويره - بالقط عبد الجبار (University of Eloued جامعة الوادي, 2024)
إنّ واقع أغلب الخطابات المسجدية اليوم في جميع ربوع ولايتنا الحبيبة وادي سوف واقع مريض، ضعيف التأثير؛ لما يفتقر إليه من مقوّمات ودعائم، مما جعل منه خطابا فارغا لا يؤدّي معشار ما يُرتقب منه؛ لذلك اهتم بعض الباحثين في مجال الدعوة بدراسته، محاولين النهوض به، وتطويره والخروج به من هذا المضيق والحضيض، إلى السّعة والتأثير، ولعلي في هذا البحث أُوفق إلى بيان سبب قصور الخطاب المسجدي، وضعف تأثيره في المخاطبين، واقتراح جملة من الحلول تعالج هذا الخلل، وقد عنونته بـ: " محدودية الخطاب المسجدي بوادي سوف وآفاق تطويره"، حاولت من خلاله الإجابة على إشكال رئيس فحواه: " لماذا الخطاب المسجدي اليوم في بلدنا محدود من جهة طروقه لبعض العلوم الإسلامية دون الأخرى، ومن جهة توجيهه لفئة دون أخرى؟"، ولبيان ذلك وتفصيله اعتمدت خطة مكونة من مقدمة للتعريف بالموضوع ومبحثين، خصصت المبحث الأول لبيان أسباب محدودية وضعف الخطاب المسجدي اليوم، وجعلت الثاني مُضمّنا جملة من الاقتراحات والحلول للنهوض به، ثم ختمت كل ذلك بخاتمة، ذكرت فيها بعض النتائج والتوصيات. ومن أهم ما أسفر عليه البحث من نتائج هو: وجوب اعتناء الخطباء والمحاضرين بجانب تنوع المادة العلمية المخاطب بها جموع المصلين، مع مراعاة حالهم، وكذا بعث الروح في الخطاب النسوي؛ بأن يُهتم به أكثر، عن طريق تنشيط المرشدات وتكثيف العمل الدعوي الموجه للنساء. Abstract : The reality of most of today's rhetoric throughout our beloved State Wade will be sick, poorly influenced; Lack of strength and backstopping, making it an empty speech that does not perform as much as anticipated; So some advocacy researchers have been interested in studying it, trying to advance it, develop it and get it out of this strait and rock bottom, to capacity and impact. In this research, I would like to agree to explain why the discourse is inadequate, its impact on the addressees is weak, and to propose a number of solutions to address this imbalance, which is titled: "The limitations of the mosque speech in Wadi will and the prospects for its development", through which I tried to answer the problem of the head of its content: "Why is the rhetoric of today's mosque in our country limited on the one hand by its ways of some Islamic sciences and not on the other, and on the other?", To illustrate and elaborate on this, I adopted a plan consisting of an introduction to the topic and researchers, which devoted the first to the reasons for today's limited and weak discourse, and made the second a set of proposals and solutions for its advancement, and then concluded with a conclusion, citing some conclusions and recommendations. One of the main findings of the research was that speakers and lecturers must take care of the diversity of the scientific material addressed to the congregation, taking into account their situation, as well as the spirit of feminist discourse; Be more interested in it, by revitalizing women guides and intensifying advocacy work for women.
Keywords: محدودية؛ الخطاب المسجدي؛ وادي سوف؛ آفاق تطويره.; imited; rhetorical rhetoric; Ouedi souf; Prospects for its development.